Supply Chain Leverage and Regulating Health and Safety Management in Shipping - Walters, David; James, Philip; Sampson, Helen; Bhattacharya, Syamantak; Xue, Conghua; Wadsworth, Emma (Relations industrielles / Industrial Relations, 2016)
The aim of paper is to understand the role and significance of supply chain leverage in promoting health and safety management at sea, the institutional contexts in which it occurs and under which circumstances it is effective.This is a qualitative research study that examined the views of seafarers and their managers on what drives the implementation of occupational health and safety (OHS) management arrangements in two shipping sectors, namely, the independent oil and chemical tanker trade and the container trade. It is based on interviews with seafarers working on board several of these vessels and with representatives of the companies managing and operating the ships.As might be anticipated from previous theorizing of supply chain effects on OHS, the study found there to be strong evidence of its influence on OHS management arrangements on tankers. The most significant driver of this effect for both managers and seafarers appeared to be the surveillance of their OHS arrangements instituted by the heads of the supply chain—in this case the oil majors and their inspection systems. Perhaps more surprisingly, despite the more diffuse, transactional and arms-length supply arrangements in the container trade, in the one case study from this sector examined in the paper, supply chain influences on OHS were nevertheless discernable. However, it also demonstrated the positive role played by the framework for maritime regulation in determining the significance of these influences.Essentially, the results indicate that, under certain conditions, supply chain relations are useful in helping to support implementation of arrangements for OHS management on merchant vessels. However, it also more broadly demonstrates that such leverage is most likely to be effective when it operates within a wider institutional framework in which public regulation and its surveillance by regulatory authorities remains a key element.